2015
DOI: 10.3390/en8077202
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Fault Permeability in Sands with Different Mineral Compositions (Evaluation of Gas Hydrate Reservoir)

Abstract: Abstract:We used a ring-shear apparatus to examine the perpendicular permeability of sands with different mineral compositions to evaluate fault behavior around gas hydrate reservoirs. The effect of effective normal stress on the permeability of two sand types was investigated under constant effective normal stresses of 0.5-8.0 MPa. Although Toyoura sand and silica sand No. 7 mainly comprise quartz, silica sand No. 7 contains small amounts of feldspar. For Toyoura sand, the permeability after ring-shearing dra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 37 publications
(57 reference statements)
0
6
0
1
Order By: Relevance
“…In order to investigate particle breakage qualitatively, the shear-zone samples after the shear test were removed for the grain-size analysis. The grain-size distribution was determined using the laser diffraction method because the samples were too small to sieve 30 . The test result shows that the proportions of clay, silt, and sand after the fast shearing at 30 mm/min were 12.5%, 45.6%, and 41.9%, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…In order to investigate particle breakage qualitatively, the shear-zone samples after the shear test were removed for the grain-size analysis. The grain-size distribution was determined using the laser diffraction method because the samples were too small to sieve 30 . The test result shows that the proportions of clay, silt, and sand after the fast shearing at 30 mm/min were 12.5%, 45.6%, and 41.9%, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Bryant et al [9] investigated the permeability changes due to the consolidation of fine-grained marine sediments in various depths and introduced empirical relations to estimate the permeability from the void ratio. Morrow et al [10], Arch and Maltman [11], Zhang and Cox [12], Crawford et al [13], and Kimura et al [14,15] investigated the effect of shearing on the permeability in order to find out permeability behavior of faults and gouge materials.…”
Section: Introductionmentioning
confidence: 99%
“…Another type of study focuses on soil permeability changes during exerted shear strain. e main methods employed in this regard are ring shear [14,18,30], rotary shear [31], and shear of a thin layer sample [10,12,13,32].…”
Section: Introductionmentioning
confidence: 99%
“…The result showed that the oil production rate was highly correlated with the fault permeability case, while the recovery factor was highest in the intermediate fault case. However, when the fault becomes less permeable, the production and the recovery factor decreased rapidly (Manzocchi et al 2008;Houwers et al 2015;Flodin and Durlofsky 2001;Kimura et al 2015;Wenning et al 2018), while Rotevatn and Fossen (2011) focused on evaluation of the subseismic fault element on the hydrocarbon exploration and production. The production and pressure data set obtained was simulated.…”
Section: Introductionmentioning
confidence: 99%